Problems of improving the legislation on land rights of foreign citizens in the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
This article discusses the issues of improving the legislation on land rights of foreign entities. The study addressed gaps in national legislation on land rights of foreign entities and provides recommendations for improvement. There were also issues of land rights of foreign citizens in the Republic of Kazakhstan and the proposed solutions to the problems of land use in the Republic of Kazakhstan.
Keywords: foreign citizens; land use; legal relations; ownership of land